2022
DOI: 10.47176/jafm.15.02.33088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Ducted Fuel Injection Strategy for Soot Reduction in Compression Ignition Engine

Abstract: The ducted fuel injection strategy is a method that significantly reduces soot emissions in direct injection compression ignition engines. Fuel is injected into the combustion chamber through a duct enhancing the airfuel mixture. It guarantees more efficient combustion and less soot formation by reducing the equivalence ratio at the autoignition zone inside the combustion chamber. The effects of the duct fuel injection on the performance, combustion, and emission of the compression ignition engine were numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Consequently in this work, they found that the combustion process of diesel was delayed with methane and after the combustion was completed, methane could not participate in the combustion reaction by accumulating in the piston ring gaps, piston crown and near the cylinder liner. Sener (2022) analyzed the influences of the grooved injection method on CI engine pollutant emission and combustion characteristics in a numerical study.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently in this work, they found that the combustion process of diesel was delayed with methane and after the combustion was completed, methane could not participate in the combustion reaction by accumulating in the piston ring gaps, piston crown and near the cylinder liner. Sener (2022) analyzed the influences of the grooved injection method on CI engine pollutant emission and combustion characteristics in a numerical study.…”
Section: Introductionmentioning
confidence: 99%